Acute Coronary Syndrome and Ischemic Heart Disease in Pregnancy: Data From the EURObservational Research Programme‐European Society of Cardiology Registry of Pregnancy and Cardiac Disease. Issue 15 (4th August 2020) - Baris, Lucia; Hakeem, Abdul; Moe, Tabitha; Cornette, Jérôme; Taha, Nasser; Farook, Fathima; Gaisin, Ilshat; Bonanomi, Carla; Parsonage, William; Johnson, Mark; Hall, Roger; Roos‐Hesselink, Jolien W.; et al.
Abstract : Background: The prevalence of ischemic heart disease (IHD) in women of child‐bearing age is rising. Data on pregnancies however are scarce. The objective is to describe the pregnancy outcomes in these women. Methods and Results: The European Society of Cardiology‐EURObservational Research Programme ROPAC (Registry of Pregnancy and Cardiac Disease) is a prospective registry in which data on pregnancies in women with heart disease were collected from 138 centers in 53 countries. Pregnant women with preexistent and pregnancy‐onset IHD were included. Primary end point were maternal cardiac events. Secondary end points were obstetric and fetal complications. There were 117 women with IHD, of which 104 had preexisting IHD. Median age was 35.5 years and 17.1% of women were smoking. There was no maternal mortality, heart failure occurred in 5 pregnancies (4.8%). Of the 104 women with preexisting IHD, 11 women suffered from acute coronary syndrome during pregnancy. ST‐segment‒elevation myocardial infarction were more common than non‒ST‐segment‒elevation myocardial infarction, and atherosclerosis was the most common etiology. Women who had undergone revascularization before pregnancy did not have less events than women who had not. There were 13 women with pregnancy‐onset IHD, in whom non‒ST‐segment‒elevation myocardial infarction was the most common. Smoking during pregnancy was associated with acute coronary syndrome. Caesarean section was the primary mode of delivery (55.8% in preexisting IHD, 84.6% in pregnancy‐onset IHD) and there were high rates of preterm births (20.2% and 38.5%, respectively). Conclusions: Women with IHD tolerate pregnancy relatively well, however there is a high rate of ischemic events and these women should therefore be considered moderate‐ to high‐risk. Ongoing cigarette smoking is associated with acute coronary syndrome during pregnancy.